Application of The Stad Type Cooperative Learning Model Towards Volleyball Underpassing Learning Outcomes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyse the application of the STAD (Student Teams-Achievement Divisions) cooperative learning model to the learning outcomes of volleyball underhand passing students at SMPN 3 Bontomarannu. The sample in this study consisted of 30 grade VII students. The study was conducted using a classroom action approach involving two cycles. In the pre-cycle, the initial evaluation showed that only 23% of students completed the learning. Then, in cycle I, improvements were made by implementing the STAD model, which resulted in 43% of students completing. In cycle II, student interaction and involvement were increased, with a total of 30 students participating. The results of the cycle I evaluation showed an average student score of 75.17 with 43% completion. However, after the implementation of improvements in cycle II, the average score increased to 80.83, with a completion percentage reaching 90%. This reflects a significant increase in students' understanding and skills in volleyball underhand passing techniques. In conclusion, the implementation of the STAD type cooperative learning model has proven effective in improving the learning outcomes of students' volleyball underhand passing at SMPN 3 Bontomarannu. Although there were challenges in the initial cycle, the improvements made in cycle II succeeded in increasing student engagement and achievement. This study suggests continuing the use of the STAD model and conducting ongoing evaluations to maximise student learning outcomes.